«Суровый стиль» в искусстве Сурена Пипояна (1960–1980-е годы) - Пипоян, Лилит (История и культура, 2026)
The art of Suren Pipoyan underwent several stages of development. Responding to the challenges of his time and in accordance with his personal aspirations, he created a unique artistic style. During the Khrushchev "Thaw," amidst the liberalization of art, Soviet artists, including Armenian ones, gained the opportunity to familiarize themselves with declassified collections of Western avant-garde art and to visit exhibitions, particularly of Mexican muralists, Picasso, Léger and others.During these years, Suren Pipoyan’s artistic style underwent significant changes, acquiring elements of Cubism and Expressionism. Combined with his academic education, this led him to the "Severe Style," which emerged in the 1960s and to which he, with some modifications, remained loyal throughout his creative career.In addition to the influences of contemporary Western art, this was also facilitated by the idea of "labor romanticism," which was widespread in the Soviet Union in the 1960s-70s, as well as the personal biography and philosophy of the artist, who endured childhood hardships and World War II. The "Severe Style," free from the polished, falsely optimistic ideas and overly detailed depictions of Socialist Realism, replaced it with a truthful and unembellished new realism.Suren Pipoyan created an entire series of multi-figure compositions [12 paintings are analysed here], whose general characteristics include labor romanticism, heroism, monumentality, and a restrained color palette. These works stand out with their geometricized forms, strong masculine figures, and expressive emotional intensity.In his paintings, Pipoyan addressed themes of labor, war, genocide, loneliness, struggle, as well as the image of the artist and intellectual.
Keywords: Суровый; стиль; армянская; советская; живопись; оттепель; Пипоян; Сурен